Le processus d’internationalisation des cégeps : Une analyse historique et géopolitique - Bégin-Caouette, Olivier (Canadian Journal of Higher Education, 2018)
The internationalization of technical education institutions is influenced by the local geopolitical context (Gallagher & Dennison, 1995). This study analyzes the evolution of international activities and organizational strategies taking place in Quebec’s collèges d’enseignement general et professionnel (CEGEPs) between 2000 and 2014, in order to identify the internationalization phase (Raby & Valeau, 2007) and assess the influence of Quebec’s geopolitical context. The data come from four surveys conducted by CEGEP International (2000, 2005, 2010) and the Federation of CEGEPs (2014), and they show a sustained growth of all international activities, but a decline in organization strategies between 2010 and 2014. We formulate the hypothesis that CEGEPs have entered a fifth and post-institutionalization phase that we called “dispersion”. A community of practice including the Government of Quebec, CEGEPs and the Federation of CEGEPs would have contributed to the growth of international activities, and recent changes in the government’s policy emphasis could explain the decline in CEGEPs’ organizational strategies.